Mitochondrial DNA diversity of the Northern Bat (Eptesicus nilssonii) in the northern Palearctic - Lempiäinen, Anna (2020)
Several factors, such as the climate fluctuations during the Pleistocene ice age, have contributed to the geographical distribution of genetic variation in contemporary populations. Phylogeography studies the variation by connecting the genetic lineages of individuals with their geographical locations. One of the most popular markers used in these studies is mitochondrial DNA (mtDNA) due to its practical qualities. Mitochondrial DNA has revealed a whole new diversity of bat species and populations compared to conventional study methods using morphology alone. The study species, the Northern Bat (Eptesicus nilssonii), is a common, widely distributed and the most northern one of the Palearctic bat species, but its entire range has not yet been studied genetically. My aim is to study the mtDNA diversity of the Northern Bat mainly in the area of Fennoscandia and Latvia and compare this data with earlier published sequences from individuals located elsewhere in the northern Palearctic to elucidate its population structure and history. The mtDNA diversity of the Northern Bat was examined from 146 individuals, of which mtDNA was sequenced of two different mtDNA markers, cytochrome b and control region. The DNA was obtained from tissue material of live bats and museum specimens. Additional data comprised 6 Northern Bat and 13 Serotine sequences. Sequences of a sister species, the Serotine (E. serotinus), were used as an outgroup. Three geographically embedded data sets from the northern Palearctic, northern Europe and Finland, were formed for examining population structure in different geographical scales. The Northern Bat population was observed to be divided into two mitochondrial lineages; one located mostly in West (European lineage) and the other in East (Siberian lineage). These lineages seem to have diverged 0.85–1.1 million years ago based on a corrected cytochrome b distance of 1.7–2.2 %. On the control region, the European lineage showed considerable genetic diversity (π = 0.019, h = 0.966), and the Siberian ...